The Long Shadow of Job Loss: Britain's Older Industrial Towns in the 21st Century - Beatty, Christina; Fothergill, Steve (Frontiers in Sociology, 2020)
This article takes a long view of economic change in Britain’s older industrial towns, drawing on the authors’ accumulated research into labour market trends in the places and communities most affected by deindustrialisation. It begins by documenting the industrial job losses over the last fifty years and their impact on unemployment, economic inactivity and welfare benefit claims, highlighting the diversion onto incapacity benefits triggered by job loss that remains a major feature of the towns. It then looks at the evidence on the present-day labour market in the towns, identifying recent job growth, though at a slower pace than in the cities, and continuing weaknesses in terms of earnings, qualifications and occupational mix. These are the on-going problems the authors describe as the ‘long shadow of job loss’. The evidence also shows that despite years of job loss, industry remains a key component of the towns’ economy and that the towns are increasingly connected to surrounding areas, including nearby cities, by strong commuting flows.